Financial accounting: International Financial Reporting Standards - THOMAS, Bill (Institutional Knowledge at Singapore Management University, 2023)
Financial Accounting, International Financial Reporting Standards puts the focus on the purpose of accounting in business. With student-friendly examples and streamlined chapters, the 12th Edition delivers a student-centric approach to learning financial accounting.While maintaining its hallmark features of accuracy and lucidity, the 12th Edition also includes updated coverage of the Conceptual Framework for Financial Reporting; new and updated financial statements; real-world examples, illustrations, and exhibits; and discussions on how the COVID-19 pandemic impacted organizations.